2012
DOI: 10.1007/s11434-012-5534-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of burial organic carbon and paleoproductivity in the Mesoproterozoic Hongshuizhuang Formation, northern North China

Abstract: In general, total organic carbon (TOC) is directly used as a proxy for paleoproductivity, however, it is not only affected by paleoproductivity, but also controlled by redox conditions and terrigenous detrital matter influx. Major and trace elements were analysed with the purpose of investigating the redox potential and paleoproductivity during deposition of the Hongshuizhuang Formation. In the present study, C-S relationship, V/Cr ratio and Mo concentration indicate that the dolomites were deposited in oxic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…TOC gives insight into palaeoproductivity. However, it may not serve as an independent proxy for palaeoproductivity as it can be controlled by redox conditions and terrigenous influx (Luo et al ., ). Schnetger et al .…”
Section: Discussionmentioning
confidence: 97%
“…TOC gives insight into palaeoproductivity. However, it may not serve as an independent proxy for palaeoproductivity as it can be controlled by redox conditions and terrigenous influx (Luo et al ., ). Schnetger et al .…”
Section: Discussionmentioning
confidence: 97%
“…The redox sensitive elemental ratios generally include V/Cr, Ni/Co, V/Ni, and Ni/Mo (Cao et al, ; Jones & Manning, ; López & Mónaco, ; López, Mónaco, Galarraga, Lira, & Cruz, ; Luo et al, ). The ionic potential of V and Cr, Ni and Co are close to each other (Railsback, ).…”
Section: Discussionmentioning
confidence: 99%
“…In oxic environments, Mo is present as stable MoO 4 2-. Conversely, in anoxic environments, S 2-can replace O 2-in MoO 4 2-and become enriched in the sediments (Crusius et al 1996;Algeo and Maynard 2004;Luo et al 2013). Crusius et al (1996) suggested that 5 -40 μg g -1 Mo implies an , showing no enrichment tendency, which indicates that the samples were deposited in an oxic environment.…”
Section: Palaeoredox Conditionmentioning
confidence: 99%
“…Paleoproductivity in a marine environment is controlled mainly by the availability of N and P (Holland 1978;Luo et al 2013;Zeng et al 2015). P is regarded as the ultimate limiting factor in marine environments and a major constituent of skeletal material and plays a fundamental role in many metabolic processes (Tyrrell 1999;Tribovillard et al 2006).…”
Section: Paleoproductivity Proxiesmentioning
confidence: 99%